High-Throughput Chromatographic and Spectroscopic Profiling for Reliable Differentiation of Hyoscyamus niger and Cleome viscosa L. - Santosh Kumar; Sapna Salar; Manju Singh; Dinesh Kumar Yadav; Anjali Singh; Mhaveer Singh (Natural Resources for Human Health, 2026)
Quality evaluation of herbal medicines is essential to ensure their safety, efficacy, and consistency. The present study focused on the quality control and authentication of Hyoscyamus niger (henbane) and its adulterant Cleome viscosa L. using modern analytical techniques. Both plants possess significant medicinal value but are often adulterated, affecting therapeutic reliability. The study aimed to differentiate and authenticate H. niger and C. viscosa through macro- and microscopic characterization, followed by chemical profiling using High-Performance Thin-Layer Chromatography (HPTLC) and High-Performance Liquid Chromatography coupled with Mass Spectroscopy (HPLC–MS). These advanced tools enabled rapid, simultaneous analysis of multiple phytoconstituents, facilitating efficient quality assessment. The results revealed distinct differences in macro- and microscopic features between the two species. Chemical profiling identified characteristic marker compounds specific to each plant, allowing clear discrimination between authentic and adulterated samples. Quantitative estimation of total alkaloid content showed a notable variation, with H. niger containing 0.1737 ± 0.0023% and C. viscosa 0.0441 ± 0.0018% (w/w). Overall, the findings highlight the effectiveness of combining high-throughput screening with advanced analytical approaches for the authentication of medicinal plants. This integrated strategy strengthens quality control measures, ensuring the authenticity, potency, and safety of herbal formulations, and supports the development of robust quality assurance protocols in the herbal industry.